Fungi and invasions in South Africa - Wood, Alan R. (African Biodiversity & Conservation, 2017)
Background: Fungi are a major component of the functioning of all terrestrial ecosystems.Objectives: To increase awareness of fungi as drivers of ecosystem processes, including invasion biology.Method: Here, I reviewed the information available regarding fungal invasions of native ecosystems in South Africa in the context of the National Status Report on Biological Invasions.Results: Only seven fungal species are regulated as invaders (all category 1b) under the National Environmental Management: Biodiversity Act (NEM:BA) A&IS regulations. Four of these species are not yet known to occur in South Africa. Similarly, under the NEM:BA A&IS regulations, two of the four species listed as prohibited (i.e. not present in the country but which would pose a threat if introduced) are already present in the country. The actual number of alien fungi in South Africa is much greater. A preliminary listing of alien fungal species is made, with a total of 9 pathogenic species known to attack indigenous plants, 11 saprotrophic species, 1 fish pathogen, 23 host-specific pathogens of listed alien terrestrial plants, 61 ectomycorrhizal species and 7 host-specific pathogens deliberately introduced as biological control agents. The majority of fungal species were introduced to South Africa most likely via the introduction of crop plants as passengers, although there are as yet very little details available on pathways of introduction into South Africa.Conclusion: For almost all aspects considered, it is concluded that there is simply not sufficient data to begin to understand the role and impact of fungal invasions in South Africa.